MANIPULATION OF INCEPTISOLS POND BOTTOM SOIL THROUGH ADDITION OF ULTISOLS AND VERTISOLS FOR REARING OF RED TILAPIA (Oreochromis sp.) LARVAE - Saberina Hasibuan; Bambang Djadmo Kertonegoro; Kamiso Handoyo Nitimulyo; Eko Hanudin (Indonesian Aquaculture Journal, 2011)
The pond bottom soil of Inceptisols mixed with Ultisols (I-U) and Vertisols (I-G) with the proportion of (70:30); (50:50); (30:70) showed the improvement of clay fractions >30% compared with the control (100% Inceptisols). These mixtures were given basal fertilizer (quail droppings manure with dosage of 2 tons/ha/month), Urea, and SP36. Cultivation system was divided into two stocked: fish ponds with 50 fish/m2 and ponds without fish. The best mix with the basal fertilizer was further treated with fertilization treatment (1 ton/ha/month of quail droppings manure) 3 times within 42 days of larval rearing. Physical and chemical soil analyses showed an increase of total soil porosity (> 50%), decrease of SG, BD, and permeability (medium), pH > 5, the CEC > 20 cmol (+) kg-1, and the C/N ratio < 6.5. The proportion of the best mix of 30% I : 70% U and 50% I : 50% G with 3 times of the fertilization frequency gave significant improvement of water quality, chlorophyll-a, diversity of plankton, benthic algae, fish growth, and total biomass. The presence of mineral montmorillonite on a mixture of 50% I : 50% G was a very good sign of the bottom soil fertility.